Advances in Social Computing and Multiagent Systems : 6th International Workshop on Collaborative Agents Research and Development, CARE 2015 and Second International Workshop on Multiagent Foundations of Social Computing, MFSC 2015, Istanbul, Turkey, May 4, 2015, revised selected papers /: 6th International Workshop on Collaborative Agents Research and Development, CARE 2015 and Second International Workshop on Multiagent Foundations of Social Computing, MFSC 2015, Istanbul, Turkey, May 4, 2015, revised selected papers. (2015) - Unknown
No abstract available